Design of invisibility cloak for unpolarized light - Zhou, Jinhui (2017)
Invisible cloaks, which used to appear as a magic item by super hero for some special goals, have been turned into reality in scientific research by the transformation optics method, especially linear transformation and conformal transformation. All the invisibility cloaks focus on nano- or micro-fabricated artificial composite materials, and for the different spatial electromagnetic properties. In this paper, the electromagnetic parameters of cloak which is suitable for particular bump and the carpet invisibility cloak based on conformal mapping are calculated. Then, using COMSOL Multiphysics simulation, I simulate the performance of the designed carpet invisibility cloak using the simplified parameters. The cloak with a particular shaped bump operates at infrared frequencies and fulfills the requirement of hiding the objects, for a special light polarization. Moreover, this paper also reported a most unusual plasmonic grating invisibility cloak based on conformal mapping, which focus more on microwave frequencies, designed to reshape negatively refracting lenses and cloaks of invisibility. The cloak overcomes the drawback of quasi-conformal mapping, where unwanted lateral shifts happens, providing the new method for design the invisibility cloak. Hence, the work broadens the ways for future applications with macroscopic cloaking devices. Keywords: Carpet invisibility cloak; Transformation optics; Metamaterial; Conformal mapping; Linear transformation